1993
DOI: 10.4269/ajtmh.1993.48.193
|View full text |Cite
|
Sign up to set email alerts
|

Iron Chelation as a Chemotherapeutic Strategy for Falciparum Malaria

Abstract: To examine the effect of iron chelation against human malaria, 37 Zambians with asymptomatic Plasmodium falciparum infections were randomly assigned to 72-hr infusions of desferrioxamine B or placebo. Mean concentrations of ring forms decreased significantly with desferrioxamine B (P < 0.001) but not with a placebo. Over seven days of observation, mean parasite concentrations remained at the initial levels in six individuals originally given placebo, but decreased promptly with administration of desferrioxamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…Inhibition of parasite growth was usually detected while in vitro cultures were being treated with the drug, but recovery of growth was observed after discontinuation of the treatment (8,27). Similar results were obtained with DFO as a therapeutic agent in humans, since most of the patients suffered from recrudescences 7 to 10 days after termination of the therapy (8).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of parasite growth was usually detected while in vitro cultures were being treated with the drug, but recovery of growth was observed after discontinuation of the treatment (8,27). Similar results were obtained with DFO as a therapeutic agent in humans, since most of the patients suffered from recrudescences 7 to 10 days after termination of the therapy (8).…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance attributed to iron metabolites in parasite toxicity, a variety of metal chelating agents such as deferoxamine and reversed siderophores has been explored as potential antimalarial chemotherapeutics (15)(16)(17)(18)(19)(20). When administered as free ligands, they have been shown to possess antimalarial activity, perhaps by disrupting ferric iron (Fe(III)) metabolism within the digestive vacuole, but none is ideal in its pharmacological properties (18).…”
mentioning
confidence: 99%
“…It was mentioned somewhere that an anti pneumocyctis effect of DFO and they had assumed a mode of action by deprivation of nutritional iron; however, they found in another study that DFO penetrates P. carinii, causing irreversible damage, thus indicating a different mode of action [8]. Pradines et al [1,14] found that iron chelator like a catecholate derived from spermidine, the N 4 -nonyl, N 1 , N 8 -bis(2,3-dihydroxybenzoyl) spermidine hydrobromide, FR160 (R = C 9 H 19 ), was the most potent against the chloroquine-susceptible clone D6 and chloroquine-resistant clone W2 of P. falciparum. FR160 acted on parasites at considerably higher rates than desferrioxamine, and at all stages of parasite growth.…”
Section: Discussionmentioning
confidence: 99%
“…Iron chelation therapy has been considered as a possible treatment for various infectious diseases [1,2]. Bhimani found that human and bovine lactoferrins (Lf) showed weak in vitro antibacterial activity while Fe-saturated lactoferrin showed no activity.…”
Section: Introductionmentioning
confidence: 99%